LANGUAGE AND IDENTITY IN ORU REFUGEE CAMP, OGUN STATE, NIGERIA (2014)
Refugees, in Oru camp, who chose integration instead of repatriation, are confronted with socio-cultural challenges which constrain them to adopt the language of their host community. Most of the previous studies on refugees investigated their socio-political and cultural concerns, with inadequate attention to their sociolinguistic challenges. Consequently, this research investigated the manifestation of identities in language use, attitudes, stereotypes and codeswitching/borrowing among Liberian and Sierra Leonean refugees in Oru Camp, Ogun State. This is with a view to evaluating the identity preferred by the refugees. This study adopted the ethnolinguistic identity theory and the mentalist theory of language attitudes. A questionnaire was administered to 240 respondents, comprising 15 teenagers (13-19yrs), 15 young adults (20-39yrs) and 10 full adults (40-60yrs), purposively drawn from each of the six ethnic groups investigated: Krahn, Bassa, Kpelle (Liberia); Mende, Temne, Limba (Sierra Leone). Thirty-six respondents comprising two teenagers, two young adults and six full adults, drawn from each ethnic group were subjected to unstructured interviews. Through participant observation, the respondents' spontaneous interactions were recorded on audio-tape and field notes. Qualitative data were subjected to ethnolinguistic analysis; quantitative data were analysed using percentages and Chi-square. Borrowings were social (terms for prostitutes, hard drugs and police) and cultural (terms for foods, trado-medicine and monarchy) as the observed respondents borrowed lexemes from Yoruba and their indigenous languages. Codeswitchings included metaphorical and emblematic types and were occasioned by greetings, quotations and proverbs. Stereotypes were negative as Liberians labelled Sierra Leoneans "violent people" while Sierra Leoneans labelled Liberians Okafrieowey (wayward). All respondents resisted being labelled omo refugee by Nigerians because it is discriminatory and preferred respectable identities like "sir" and "madam". The reasons for minimal use of indigenous languages were the prestige of English and accommodation, while the minimal use of Yoruba was mainly due to negative attitude of host community. In terms of language attitude, an average of 72.2% of teenagers and 100% of young adults valued their indigenous languages without speaking them; 100% of full adults valued their indigenous languages but seldom used them; 80.0% of young adults and 88.8% of full adults undervalued Yoruba and did not speak it. In respect of language use at home, an average of 100% of young adults and 88.7% of full adults used English/pidgin/krio in parent-child interaction while 8.3% of full adults used English/indigenous languages. With regard to neighbourhood, 100% of young adults and teenagers, and 70.0% of full adults used English/pidgin/krio in intra-ethnic interaction while 30.0% of full adults used indigenous languages/pidgin/krio. With reference to school, 100% of teenagers used English in classroom and English/ Yoruba during break time. The significant value of x^2= 12.61; df =2, p< 0.05; (home) and, x^2= 15.86; df= 2, p<0.05 (neighbourhood) suggests that age influenced language use rather than ethnicity. Oru refugees manifest multiple linguistic identities but prefer a modern identity represented by English more than an ethnic/Yoruba identity. Refugees in Oru camp, who opted for integration, need to identify more with Yoruba for purposes of inclusion and the benefits of diversity.